Critical View of Novel Treatment Strategies for Glioblastoma: Failure and Success of Resistance Mechanisms by Glioblastoma Cells - Burster, Timo; Traut, Rebecca; Yermekkyzy, Zhanerke; Mayer, Katja; Westhoff, Mike-Andrew; Bischof, Joachim; Knippschild, Uwe (Frontiers in Cell and Developmental Biology, 2021)
According to the invasive nature of glioblastoma, which is the most common form of malignant brain tumor, the standard care by surgery, chemo- and radiotherapy is very challenging. The presence of glioblastoma stem cells (GSCs) and the surrounding tumor microenvironment protects glioblastoma from recognition by the immune system. Conventional therapy concepts have failed to completely remove glioblastoma cells, which is one major drawback in clinical management of the disease. The use of small molecule inhibitors, immunomodulators, immunotherapy, including peptide and mRNA vaccines, and virotherapy came into focus for the treatment of glioblastoma. Although novel strategies underline the benefit for anti-tumor effectiveness, serious challenges need to be overcome to successfully manage tumorigenesis, indicating the significance of developing new strategies. Therefore, we provide insights into the application of different medications in combination to boost the host immune system to interfere with immune evasion of glioblastoma cells which are promising prerequisites for therapeutic approaches to treat glioblastoma patients.